Birth Control Sabotage Motivation and Measurement: A Mixed-Methods Analysis among Latina Women - Grace, Karen Trister; Glass, Nancy E.; Miller, Elizabeth; Alexander, Kamila A.; Holliday, Charvonne N.; Decker, Michele R (Violence against women, 2024)
Reproductive coercion (RC) is a type of intimate partner violence that includes birth control sabotage (BCS). We explored the perceived intent behind BCS to refine RC measurement, using a mixed-methods design with a clinic-based sample of Latina women (13 interviews; 482 surveys). Women perceived partners used BCS for reasons beyond pregnancy promotion. Specifically, 16.8% of participants reported any past-year RC; this decreased to 9.5% when asked if their partner used BCS with the sole intent of getting them pregnant. RC measures and assessment should separate behavior from intent in BCS questions to not underestimate the prevalence and to guide clinical response.